2019 International Conference on Robotics and Automation (ICRA) 2019
DOI: 10.1109/icra.2019.8794032
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Humanoid Contact Planning using Learned Centroidal Dynamics Prediction

Abstract: Humanoid robots dynamically navigate an environment by interacting with it via contact wrenches exerted at intermittent contact poses. Therefore, it is important to consider dynamics when planning a contact sequence. Traditional contact planning approaches assume a quasi-static balance criterion to reduce the computational challenges of selecting a contact sequence over a rough terrain. This however limits the applicability of the approach when dynamic motions are required, such as when walking down a steep sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 50 publications
(85 reference statements)
0
32
0
Order By: Relevance
“…For example, legged robots can use more favorable leg stiffness control to adapt to different terrain after obtaining the terrain stiffness information [1,2]. They can achieve better body balance to walk safely on the terrain with the friction information [3][4][5]. Wheeled robots can thus avoid excessive wheel slip and sinking.…”
Section: Introductionmentioning
confidence: 99%
“…For example, legged robots can use more favorable leg stiffness control to adapt to different terrain after obtaining the terrain stiffness information [1,2]. They can achieve better body balance to walk safely on the terrain with the friction information [3][4][5]. Wheeled robots can thus avoid excessive wheel slip and sinking.…”
Section: Introductionmentioning
confidence: 99%
“…One of the areas our approach is most lacking is a consideration of the CoM dynamics, as in [10]. While it is unclear if the learned-type dynamic cost prediction presented in that work is necessarily the best approach, it is certainly promising for producing plans that are dynamically variable to the environment structure.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…More recently, a traversibility metric has been used to guide the expansion of ANA* planners to help accelerate convergence for multicontact planning [9]. Additionally, it has been shown that by including an estimated dynamics edge cost, the resulting plans can better adapt to the demands of different environments on the center of mass (CoM) dynamics [10]. A planar region segmentation of the environment has also been used to extract a desired 2D body path plan for the robot, and directly used to compute the desired footholds by assuming flat ground [8].…”
Section: Related Workmentioning
confidence: 99%
“…We assume there is a 0.4 second long swing phase followed by 0.6 second double support phase for each contact transition. We follow our previous work [7], given S(s), S(s ), r(s) and l(s), we use neural networks to predict dynamic feasibility of the contact transition, and determine r(s ) and l(s ).…”
Section: Anytime Discrete-search Contact Plannermentioning
confidence: 99%
“…Our goal is to maximize P success (T cp ), which can be achieved by minimizing K k=1 −log (P success (ε k )). Therefore, we define c cap as c cap (s, s ) = −log (P success (ε(s, s ))) (7) With this definition of c cap , we can find a path with maximum success rate by minimizing the total capturability cost of the path, which is done by the ANA* algorithm. In practice, we set w cap w s , d(s, s ) to let ANA* focus on maximizing P success (T cp ).…”
Section: B Capturability Costmentioning
confidence: 99%